2018
DOI: 10.1371/journal.pone.0200390
|View full text |Cite
|
Sign up to set email alerts
|

Molecular marker sequences of cattle Cooperia species identify Cooperia spatulata as a morphotype of Cooperia punctata

Abstract: The genus Cooperia includes important parasites of ruminants and currently contains 34 accepted species. However, even for those species infecting livestock, there is a considerable lack of molecular information and many species are only identifiable using subtle morphological traits. The present study aimed to provide molecular data to allow diagnosis of Cooperia species infecting cattle. Partial sequences of two mitochondrial (cytochrome oxidase 2, 12S rRNA gene) and two nuclear genes (isotype 1 β tubulin ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 47 publications
3
20
0
Order By: Relevance
“…This indicates that ITS2 sequences are not suitable to address taxonomic or even phylogenetic questions within the genus Marshallagia. This is in agreement with other recent studies analyzing closely related strongyle nematodes showing that ITS2 is an excellent marker to identify the genus, but that closely related species differ only minimally in their ITS2 sequence and that the phylogenetic signal obtained from ITS2 sequences of Marshallagia specimen was not reliable [13,14].…”
Section: Internal Transcribed Spacersupporting
confidence: 92%
See 1 more Smart Citation
“…This indicates that ITS2 sequences are not suitable to address taxonomic or even phylogenetic questions within the genus Marshallagia. This is in agreement with other recent studies analyzing closely related strongyle nematodes showing that ITS2 is an excellent marker to identify the genus, but that closely related species differ only minimally in their ITS2 sequence and that the phylogenetic signal obtained from ITS2 sequences of Marshallagia specimen was not reliable [13,14].…”
Section: Internal Transcribed Spacersupporting
confidence: 92%
“…Recent work on Cooperia spp. (Cooperiidae, Cooperinae) and C. minutus (Strongylidae, Cyathostominae) revealed that combined analyses of mitochondrial and nuclear marker sequences improved species identification and phylogenetic analyses [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…This information is marked in Table 1. Later on, several other species were originally described, re-described, synonymised with congeners, or designated as species inquirendae (Isenstein, 1971a;Lichtenfels, 1977;Gibbons, 1981;Newton et al, 1998;Ramünke et al, 2018). For instance, Gibbons published in 1981 a merit work revising African species of the genus Cooperia.…”
Section: Referencesmentioning
confidence: 99%
“…Nevertheless, the invalidity of C. surnabada was finally accepted by Gibbons (1981), Humbert & Cabaret (1995), Lichtenfels et al (1997), Newton et al (1998), and Raműnke et al (2018) ( Table 1). Cooperia mcmasteri was initially synonymized with C. surnabada by Karamendin (1967) and Lichtenfels (1977) and then later, with C. oncophora (Ramünke et al, 2018). Two other morphologically similar species are C. spatulata and C. punctata (Table 1).…”
Section: Referencesmentioning
confidence: 99%
See 1 more Smart Citation